2019
DOI: 10.1002/msc.1390
|View full text |Cite
|
Sign up to set email alerts
|

Experienced barriers in shared decision‐making behaviour of orthopaedic surgery residents compared with orthopaedic surgeons

Abstract: IntroductionIn shared decision‐making (SDM), physicians encourage the patient to participate in the care process. The theory of planned behaviour describes that behaviour is dependent on intention. In its turn, intention is explained by attitude, subjective norm and perceived behavioural control. In orthopaedics, little is known about current SDM behaviour and how to promote it.The aim of the present study was to gain insight into the SDM behaviour of orthopaedic residents and supervisors by measuring levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The reasons for their 'paternalism preference' remain unclear. It has been shown that residents and junior doctors feel uncertain about applying SDM in their encounters with patients [17][18][19], which may contribute to their preference for paternalistic decision making. To our knowledge the relationship between residents' uncertainty and their decision-making behavior in medical encounters has not been studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for their 'paternalism preference' remain unclear. It has been shown that residents and junior doctors feel uncertain about applying SDM in their encounters with patients [17][18][19], which may contribute to their preference for paternalistic decision making. To our knowledge the relationship between residents' uncertainty and their decision-making behavior in medical encounters has not been studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that the intention to engage in SDM among physicians varies between settings and disciplines. 26,27 In this study, dermatologists who served at private healthcare settings had higher SDM sore and stimulus score, but had lower barrier score in SDM implementation than those who served at public healthcare settings. The results for institution type are in alignment with the previous studies that the type of care provided by different institutions would influence the extent to which dermatologists and patients actually participate in decision-making.…”
Section: Discussionmentioning
confidence: 58%
“…It has previously been suggested that a non-surgical treatment decision taken by an orthopaedic surgeon is related to greater experience and a less macho attitude towards surgery [ 27 ], yet the present results show that patients and orthopaedic surgeons seem to have different opinions about the decision-making process, in terms of patient involvement. Orthopaedic surgeons are in general willing to be involved in a shared decision-making process [ 28 ], although it is a barrier that they are concerned that it is more time consuming [ 29 ]. Research shows that both healthcare personnel and patients prefer a SDM management [ 30 ], and when they are provided with information about the injury and treatment options, patients are more likely to be involved in their healthcare decisions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%